Geographic origin is not supported by the genetic variability found in a large living collection of Jatropha curcas with accessions from three continents. Issue 4 (19th January 2015) - Maghuly, Fatemeh; Jankowicz‐Cieslak, Joanna; Pabinger, Stephan; Till, Bradley J.; Laimer, Margit
Abstract Increasing economic interest in Jatropha curcas requires a major research focus on the genetic background and geographic origin of this non‐edible biofuel crop. To determine the worldwide genetic structure of this species, amplified fragment length polymorphisms, inter simple sequence repeats, and novel single nucleotide polymorphisms (SNPs) were employed for a large collection of 907 J. curcas accessions and related species (RS) from three continents, 15 countries and 53 regions. PCoA, phenogram, and cophenetic analyses separated RS from two J. curcas groups. Accessions from Mexico, Bolivia, Paraguay, Kenya, and Ethiopia with unknown origins were found in both groups. In general, there was a considerable overlap between individuals from different regions and countries. The Bayesian approach using STRUCTURE demonstrated two groups with a low genetic variation. Analysis of molecular varience revealed significant variation among individuals within populations. SNPs found by in silico analyses of Δ12 fatty acid desaturase indicated possible changes in gene expression and thus in fatty acid profiles. SNP variation was higher in the curcin gene compared to genes involved in oil production. Novel SNPs allowed separating toxic, non‐toxic, and Mexican accessions. The present study confirms that human activities had a major influence on the genetic diversity of J. curcas, not only because of domestication, but also because of biased selection.